THE EFFECT OF MAKE A MATCH LEARNING MODEL ASSOCIATED WITH VIDEO MEDIA ON THE ABILITY TO UNDERSTAND SCIENCES CONCEPT FOR V GRADE ELEMENTARY SCHOOL - Andriani Andriani; Dina Anika Marhayani; Erdi Guna Utama (PROGRES PENDIDIKAN, 2022)
This study aims to determine the differences in using the Make A Match learning model assisted by learning video media on the ability to understand science concepts in fifth-grade elementary school. The type of research used is quantitative with a quasi-experimental type of experimental method in the form of a nonequivalent control group design. The research population was all fifth-grade students of SDN 18 Senturan, with a sampling technique in the form of a saturated sample technique (total sampling). This study used two classes, namely the experimental class, which was treated using the Make A Match learning model assisted by video learning media, totaling 24 students, and the control class using conventional methods totaling 24 students. The study results can be concluded that: (1) There are differences in learning outcomes between the experimental class, which was given treatment using the make-a-match learning model assisted by video media, and the control class, which was given conventional methods. Because there are differences, there is an effect of learning outcomes for the experimental class and the control class on the science lesson on how the body processes food for the fifth-grade students of SDN 18 Senturang, which was analyzed using the t-test parametric statistical test with count = 2.167 > table = 2.012. (2) Make learning model A Match assisted by video media has an influence on the learning outcomes of science material on how the body processes food for the fifth-grade students of SDN 18 Senturan by 0.98 with high criteria.